Equine Respiratory Medicine and Cardiology - Ferrucci, Francesco; Feudo, Chiara Maria Lo; Stucchi, Luca (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Recent years have seen growing interest in equine lung and heart health, and advances in technology and a focus on equine welfare have driven this research. This Special Issue explores novel diagnostic and therapeutic approaches, including imaging techniques and lung function testing, immunological features, and immunomodulatory treatments for equine asthma and common racehorse respiratory issues. Moreover, it reports on novel echocardiography data of donkeys. This collection offers valuable insights into equine cardio-respiratory medicine.